Slavery and Secession in Arkansas : A Documentary History - Gigantino, James J. (Book collections on Project MUSE., 2015)
The absorbing documents collected in Slavery and Secession in Arkansas trace Arkansas's tortuous road to secession and war. Drawn from contemporary pamphlets, broadsides, legislative debates, public addresses, newspapers, and private correspondence, these accounts show the intricate twists and turns of the political drama in Arkansas between early 1859 and the summer of 1861. From an early warning of what Republican political dominance would mean for the South, through the initial rejection of secession, to Arkansas's final abandonment of the Union, readers, even while knowing the eventual out.